Quality of life at machine operators of agriculture - T. A. Novikova; N. A. Mikhaylova; G. A. Bezrukova; S. S. Raykin (Acta Biomedica Scientifica)
The purpose this research was to investigate the quality of life machine operators of agriculture, depending on the status of the age and length of service in the profession. To assess the quality of life was used widely used international Russian-language health a validated questionnaire SF-36. Studies have been conducted practically healthy quality of life (based on the results of periodic medical examinations) machine operators of agriculture Saratov region (102 people) aged 30 to 59 years of experience in the profession from 3 to 35 years. Average values of an indicator for age groups 2 and 3 made "the general health", respectively, 95,2 and 78,7 % from level characteristic for younger age group. Intergroup distinction was noted between average sizes of this indicator at persons at the age of 30-39 years and 50-59 years, and also 40-49 summer machine operators and workers of advanced age (50-59 years). 1t is established that with increase in calendar age at machine operators of agriculture statistically significant decrease in values of indicators of quality of life to scales the general health, physical functioning, physical and role functioning and viability. With increase in length of service at machine operators decrease in values of indicators of physical functioning and role physical functioning. A statistically significant weak negative correlation between the level of quality of life, age (r = -0,39) and professional experience (r = -0,31). 1n this case, the highest correlation between the age of the examined patients and quality of life was typical of the general health scale (r = -0,37), physical functioning (r = -0,41), and role physical functioning (r = -0,34). Professional experience correlated with the level of physical functioning (r = -0,30) and role^hysical functioning (r = -0,32), has practically no effect on the subjective assessment of general health (r = -0,22). Results of researches allow recommending questionnaire SF-36 use when forming individual and group improving programs for machine operators of agricultural production.